The influence of individual characteristics on perceived restorativeness and benefits associated with exposure to nature in a garden - Sella, Enrico; Meneghetti, Chiara; Muffato, Veronica; Borella, Erika; Carbone, Elena; Cavalli, Raffaele; Pazzaglia, Francesca (Frontiers in Psychology, 2023)
This study newly explored the relationship between individual characteristics (i.e., connectedness to nature, a preference for natural rather than built environments, personality, visuospatial preferences) with perceived restorativeness, as well as affective and memory-related benefits of exposure to the nature. Eighty adults were individually exposed to nature by walking in a landscape garden. Measures of connectedness to nature, preference for natural environments, personality traits, and visuospatial preferences were administered. Before and after walking in the garden, participants completed measures of affect (positive and negative emotions) and memory (short-term and working memory, and spatial memory). After walking they completed a Perceived Restorativeness scale. Perceived Restorativeness was found to be significantly explained by Extraversion (personality trait) and Connectedness to Nature. There was no significant influence of individual characteristics on benefits to affect and memory measures. Overall, the results showed that perception of the restorative effect of a natural environment is related to connectedness to nature and personality (extraversion trait). Taken together, our findings highlight the importance of considering individual characteristics to better capture restorative/recovery effects of a natural environment in an individual, and to tailor/implement nature-based solutions to ensure a sustainable urban green environment and to promote quality of life for their citizens.